Transforming Data with Ontology and Word Embedding for an Efficient Classification Framework - Nguyen, Thi Thanh Sang; Do, Pham Minh Thu; Nguyen, Thanh Tuan; Quan, Thanh Tho (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2023)
Transforming data into appropriate formats is crucial because it can speed up the training process and enhance the performance of classification algorithms. It is, however, challenging due to the complicated process, resource-intensive and preserved meaning of the data. This study proposes new approaches to building knowledge representation models using word-embedding and ontology techniques, which can transform text data into digital data and still keep semantic/context information of themselves in order to enhance modeling data later. To evaluate the effectiveness of the built models, a classification framework is proposed and performed on a public real dataset. Experimental results show that the constructed knowledge representation models contribute significantly to the performance of classification methods.
Keywords: ontology; Onto2Vec; Doc2Vec; Classification